Análisis comparativo de la contribución ambiental, económica y social, en los procesos de fabricación de cuero Wetblue (Ribera y Curtido) para tres estados productivos. (2019)
This research seeks to analyze the level of social, economic and environmental contribution of the Ribera and Curtido processes in a leather company in Antioquia, compared to its previous processes of purchase of Wetblue leather. To carry it out, the industrial production processes are characterized, the key qualitative and quantitative evaluation parameters are described and finally a comparative analysis of the manufacturing processes is performed. The company under study developed three productive states to obtain Wetblue leather, productive status 0: purchase of Wetblue leather (market state analysis), productive status 1: Production with technology acquired for the manufacture of Wetblue leather (initial stage of adaptation) and Productive State 2: Production with technology acquired (Stage of maturity) for the manufacture of Wetblue leather. The analysis is based on a comparative case study based on qualitative and quantitative parameters identified as representative for this production process, the normalization step is performed and the application of the hierarchical process analysis (AHP) methodology. The correlated results are obtained to obtain the most sustainable alternative, concluding that the improvement process for the case study satisfactorily and integrally beneficiaries the improvement for obtaining Wetblue leather.